Pengaruh Promosi dan Kualitas Pelayanan Terhadap Keputusan Konsumen dalam Menggunakan Layanan Go-Food di Kota Padang Selama Masa pandemi covid-19 - Maria Magdalena; Arpen Arpen (JURNAL PUNDI, 2022)
The purpose of this study is to investigate the effect of promotion and service on consumer choice when using food services in Padang City during the Covid-19 pandemic with a case study on the Gunung Pangilun community. The research involves quantitative research, the population of this research is the public and students of Padang city who used Go-Jek in Go-Food services. In this study population, there were 14,700 service users from January to June. The sampling method used in this study was non-probability sampling. The non-probability sampling method used in this study was random sampling. The number of samples collected in this study was 60 people. respondents. Data analysis techniques used validity testing, reliability testing, descriptive analysis (TCR testing), classical hypothesis/assumption testing, multiple linear regression analysis and hypothesis testing. The results of this study show that promotion, physical evidence, reliability, responsiveness, assurance, and empathy have a positive and significant impact on consumer decision on  the use of  Go-Food services during the Covid-19 pandemic in Gunung Pangilun, Padang city. Keywords: Promotion, Service Quality, Consumer Decision, Go-Food.